Organic functions in everyday life: Nail polish as a pedagogical resource (Research, Society and Development, 2025)
The aim of this article is to present the results of a study that investigated students' difficulties in establishing connections between organic functions and nail polish, a cosmetic widely used in daily life. To address this issue, the thematic workshop “Identification of Organic Compounds in Nail Polish” was developed and applied to 28 third-year high school students from a public school in the district of Ibitira, municipality of Rio do Antônio/BA. The research employed questionnaires with open and closed-ended questions, administered before and after the workshop, to assess the impact of the activity on students’ learning. The results indicated that the contextualized approach significantly contributed to the understanding of organic chemistry concepts, promoting greater student engagement and active participation in the teaching-learning process. Statistical analysis, using the McNemar test at a 5% significance level, revealed significant advances in knowledge about organic functions and their application in everyday life, reinforcing the relevance of thematic workshops as na innovative pedagogical strategy. It is concluded that the use of active methodologies, combined with content contextualization, can facilitate learning and stimulate students’ interest in chemistry, making teaching more dynamic and meaningful. Thus, the thematic workshop proved to be na effective tool for strengthening the connection between theory and practice, contributing to the development of more critical and participative students.